New approaches and models of press service organization - Serdali, Б.К.; Yertassova, Г.Қ. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2022)
The communication of the press service with the external target audience is clearly planned with internal departments and is determined in accordance with the tasks that each of them performs. An example of such sustainable management is the activity of the press service of the President of the Republic of Kazakhstan in information and public relations. The structure of the official activities of the staff of the press service of the Presidential Office is clearly and clearly delineated. Unfortunately, the press service of a number of structures is engaged in auxiliary activities that are not part of its field of activity: advertising, PR, GR, marketing, product promotion, etc. In most cases, this task arises from objective circumstances, i.e. due to lack of funds. Basically, a specific system defining the tasks of the press service should be formed depending on the technology of the work performed. In the conditions of Kazakhstan, such activities arise due to a lack of understanding of the causes and consequences, ignorance of employees of their instructions. The article dealt with a number of issues that give instructions for the effective and sustainable work of the press service in the field of PR.